Psychological states and working conditions buffer beginning teachers' intention to leave the job. Issue 1 (1st January 2017) - De Neve, Debbie; Devos, Geert
Abstract: The high turnover rates of beginning teachers are an issue of continuing concern in education. However, little is known about the motivational process that encourages beginning teachers to stay in the teaching profession. This study investigated how working conditions (job insecurity, teacher autonomy, collective responsibility, reflective dialogue, and deprivatised practice) and psychological states (teacher self-efficacy and affective commitment) influence turnover intentions. A sample of 272 beginning teachers from 72 Flemish (Belgian) primary schools was recruited for this questionnaire-based study. Path analysis revealed that teacher self-efficacy and affective commitment directly reduced the intention to leave the job. Furthermore, teacher self-efficacy and affective commitment fully mediated the relationships between teacher autonomy and the intention to leave the job and collective responsibility and the intention to leave the job. These findings provide insight into the underlying psychological processes of beginning teachers to leave education.